Implementasi Active Directory Berbasis Open Source Menggunakan Linux dan Samba 4 - Agus Fatulloh; Irfan Fauzan (Universitas Budi Luhur, 2020)
Personal data storage performed by each user on a computer in a company has a high risk of data loss or damage. Loss and damage to data is due to data theft or damage to data storage devices on the computer. Lack of user awareness because not all users have knowledge of information technology, data management carried out personally by each user has a very high risk of damage and data loss, which is caused by damaged data storage devices or data theft by unauthorized parties. Active Directory Samba 4 and Linux are centralized data storage solutions (all user data will be stored on the server) by authenticating access to user data according to their ownership. The method used to build an Active Directory Samba 4 and Linux Server is the Network Development Life Cycle. All user data can be stored and accessed properly according to the policies set in Active Directory Samba 4 and Linux .